1999
DOI: 10.1046/j.1365-2516.1999.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Health status and satisfaction of asymptomatic HIV‐positive haemophiliacs in Kyushu, Japan

Abstract: The purpose of this study was to elucidate the effects of human immunodeficiency virus (HIV) on haemophiliacs with physical functional disabilities induced by haemophilia in Kyushu, Japan. The subjects were 38 adult haemophiliacs who were selected from 129 patients registered with the North Kyushu Haemophilia Centre. They were divided into 21 asymptomatic HIV-positive and 17 HIV-negative adult haemophiliacs. Coagulation factor levels, modified DePalma classification, Arthritis Impact Measurement Scale 2 (AIMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Tanaka et al . [30] and Triemstra et al . [31] selected various types of patient‐reported outcomes instruments to address various aspects of the ‘well‐being’ of haemophilia patients.…”
Section: Other Scalesmentioning
confidence: 99%
“…Tanaka et al . [30] and Triemstra et al . [31] selected various types of patient‐reported outcomes instruments to address various aspects of the ‘well‐being’ of haemophilia patients.…”
Section: Other Scalesmentioning
confidence: 99%
“…Tanaka et al . [25] used the AIMS2 and a Satisfaction with Daily Life (SDL) questionnaire to evaluate QoL in 21 asymptomatic HIV positive and 17 HIV negative patients. The AIMS2 demonstrated that the HIV positive patients were significantly more dissatisfied with social activities and had lower mood.…”
Section: Evaluation Of Quality Of Life (Qol)mentioning
confidence: 99%
“…The SDL questionnaire identified more differences than the AIMS2 and was therefore considered to be more responsive. There were no significant differences between the groups in overall satisfaction or health perception [25]. There were also no differences in the clinical severity of arthropathy between groups; however, this was only determined by X‐ray changes that may not be a sensitive measure of clinical symptoms [26].…”
Section: Evaluation Of Quality Of Life (Qol)mentioning
confidence: 99%
“…SDL had seven items on a 5-point scale, and was revised to have 11 items on a 5-point scale in order to make this universally adaptable to elderly persons, based on the results of a random sampling study on the factors involved in the satisfaction of daily living for elderly individuals living at home [7]. Later, we also proved the validity of SDL in using for patients with stroke living at home [8], elderly persons living at home [9] and hemophiliacs [10].…”
Section: Introductionmentioning
confidence: 99%